GmTRAB1, a Basic Leucine Zipper Transcription Factor, Positively Regulates Drought Tolerance in Soybean (Glycine max. L) - Hui Li; Qiu-Yu Zhang; Ping Xu; Xiao-Hua Wang; Sheng-Jie Dai; Zhen-Ning Liu; Meng Xu; Xue Cao; Xiao-Yu Cui (Plants)
The basic leucine zipper (bZIP) transcription factors play crucial roles in plant resistance to environmental challenges, but the biological functions of soybean bZIP members are still unclear. In this study, a drought-related soybean bZIP gene, GmTRAB1, was analyzed. The transcript of GmTRAB1 was upregulated under drought, ABA, and oxidative stresses. Overexpression of GmTRAB1 improved the osmotic stress tolerance of transgenic Arabidopsis and soybean hairy roots associated with increased proline content and activity of antioxidant enzymes and reduced accumulations of malonaldehyde and reactive oxide species. However, RNA interference silencing of GmTRAB1 in the soybean hairy roots improved drought sensitivity. Furthermore, GmTRAB1 increased the sensitivity of transgenic plants to ABA and participated in modulating ABA-regulated stomatal closure upon drought stress. In addition, GmTRAB1 stimulated the transcript accumulation of drought-, ABA-, and antioxidant-related genes to respond to drought. Collectively, this research will contribute to understanding the molecular mechanisms of bZIP transcription factors in soybean’s resistance to drought.